FATTY ACID COMPOSITION OF LONGISSIMUS DORSI AND SEMIMEMBRANOSUS MUSCLES DURING STORAGE IN LAMBS REARED INDOORS AND ON PASTURE - Popova, T. (Emirates Journal of Food and Agriculture, 2013)
The changes of the fatty acid profile during frozen storage of Longissimus dorsi (LD) and Semimembranosus (SM) muscles were studied in ram lambs according to the rearing systems (indoors and on pasture) and breed (Northeastern Bulgarian Fine Wool Breed and cross of this breed with Ile de France). Both muscles in the pastured lambs had higher content of C18:3 and total CLA while the content of C20:5 was significantly higher in the SM (P<0.05). The crossbred lambs displayed higher content of oleic acid and total monounsaturated fatty acids (MUFA) in the LD (P<0.05) as well as higher content of C16:0 in the SM (P<0.05). Both muscles of the lambs of the cross had lower content of C18:2 and polyunsaturated fatty acids (PUFA). The duration of frozen storage led to lower total content of saturated fatty acids (P<0.05) and higher amount of MUFA and PUFA through the course of the storage as the influence was stronger in the SM.